Bio-modification of coal fly ash using urease-producing bacteria. (15th February 2021) - Zhang, Junke; Wen, Kejun; Li, Lin
Abstract: Due to its potential for metal leaching and the corresponding environmental impacts, the beneficial reuse of coal fly ash in construction has been carefully evaluated. Biological processing may provide a promising technology to modify coal ash to limit metal leaching. The goal of this study was to use urease-producing bacteria to modify coal fly ash and to evaluate the effect on metal leaching. Metal leaching was investigated through synthetic precipitate leaching processes by three types of coal fly ash before and after bio-modification. For metals like Al, Ba, and Cr, the leaching concentrations decreased after bio-modification, whereas the leaching concentrations increased for metals such as Ca, Mg, Mn and V. The increase of pH and the production of carbonate by the consumption of urea and the adsorption to precipitation compounds during the bio-modification process contributed the stabilization of Al, Ba and Cr. However, the bio-leaching induced by the organic products from bacteria and potentially the competition for carbonates promoted the leaching of Ca, Mg, Mn and V which would benefit the recycle of metals. Bioprocessed coal fly ash and sand mixtures were utilized to prepare construction materials. The unconfined compressive and flexural strength supports beneficial uses of coal fly ash with bio-modification.